2015
DOI: 10.1001/jamapsychiatry.2015.1813
|View full text |Cite
|
Sign up to set email alerts
|

Self-blame–Selective Hyperconnectivity Between Anterior Temporal and Subgenual Cortices and Prediction of Recurrent Depressive Episodes

Abstract: IMPORTANCE Patients with remitted major depressive disorder (MDD) were previously found to display abnormal functional magnetic resonance imaging connectivity (fMRI) between the right superior anterior temporal lobe (RSATL) and the subgenual cingulate cortex and adjacent septal region (SCSR) when experiencing self-blaming emotions relative to emotions related to blaming others (eg, "indignation or anger toward others"). This finding provided the first neural signature of biases toward overgeneralized self-blam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
110
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(119 citation statements)
references
References 60 publications
5
110
1
Order By: Relevance
“…Self-blame versus other-blaming emotions predict subsequent recurrence of depressive episodes and are associated with hyperconnectivity between anterior temporal and subgenual brain cortices as measured by functional magnetic resonance imaging. 11 Additionally, from the findings in this study, we note that the perception of vasomotor and sleep disturbances, although frequent in this population of women, did not contribute significantly to the development of depressive illness. Thus, this finding does not lend support to the ''domino'' hypothesis of perimenopausal depression that postulates that vasomotor symptoms causing sleep disturbances trigger depressive illness at this vulnerable time.…”
supporting
confidence: 43%
“…Self-blame versus other-blaming emotions predict subsequent recurrence of depressive episodes and are associated with hyperconnectivity between anterior temporal and subgenual brain cortices as measured by functional magnetic resonance imaging. 11 Additionally, from the findings in this study, we note that the perception of vasomotor and sleep disturbances, although frequent in this population of women, did not contribute significantly to the development of depressive illness. Thus, this finding does not lend support to the ''domino'' hypothesis of perimenopausal depression that postulates that vasomotor symptoms causing sleep disturbances trigger depressive illness at this vulnerable time.…”
supporting
confidence: 43%
“…This should be addressed as such measurements hold great promise in predicting individual outcomes. Farb et al (2011), for instance, found that a simple functional magnetic resonance imaging (fMRI) measure coupled with an emotion manipulation (sad movies) could near perfectly predict relapse overall independently of treatment, and Lythe et al (2015) found that self-blame-related fMRI connectivity features had predictive validity. Other neurobiological features might relate to specific treatments.…”
Section: Resultsmentioning
confidence: 99%
“…This has shown some promising recent results, indicating that it may become possible to predict individual trajectories of patients with schizophrenia (Anticevic et al, 2015) or mood disorders (Lythe et al, 2015;Schmaal et al, 2015) from neuroimaging data, or forecast individual treatment responses to psychotherapy (Mansson et al, 2015), antidepressants (DeBattista et al, 2011;McGrath et al, 2013;Miller et al, 2013) and antipsychotics (Hadley et al, 2014;Nejad et al, 2013).…”
Section: Accepted Manuscriptmentioning
confidence: 99%